Broadening access to cryoEM through centralized facilities. Issue 2 (February 2022) - Zimanyi, Christina M.; Kopylov, Mykhailo; Potter, Clinton S.; Carragher, Bridget; Eng, Edward T.
Abstract : Cryogenic electron microscopy (cryoEM) uses images of frozen hydrated biological specimens to produce macromolecular structures, opening up previously inaccessible levels of biological organization to high-resolution structural analysis. CryoEM has the potential for broad impact in biomedical research, including basic cell, molecular, and structural biology, and increasingly in drug discovery and vaccine development. Recent advances have led to the expansion of molecular and cellular structure determination at an exponential rate. National and regional centers have emerged to support this growth by increasing the accessibility of cryoEM throughout the biomedical research community. Through cooperation and synergy, these centers form a network of resources that accelerate the adoption of best practices for access and training and establish sustainable workflows to build future research capacity. Highlights: Cryogenic electron microscopy (cryoEM) and cryogenic electron tomography (cryoET) are revealing structures of medically relevant biomolecules at an ever-increasing pace, though the technique is still undergoing rapid development, increasing the barrier to entry. Large collaborative centers drive the standardization of workflows, lowering the barrier to entry as the colocalization of technologists and biologists drives the development of useful technology to simplify and speed workflows in a way that increases accessibility to the techniques. Significant contributions in the structural characterization of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins highlight the success of collaborative cryoEM centers. Cross-training at cryoEM centers allows practitioners to enter the field at varied levels, increasing the impact of the technique in diverse research areas; such centers also promote a sustaining community by building bridges and providing resources in a collaborative environment.